The parathyroids : basic and clinical concepts - Bilezikian, John P.; Marcus, Robert (Physician); Levine, Michael A., 1950-; Marcocci, Claudio; Silverberg, Shonni J.; Potts, John T., 1932- (Elsevier science & technology books., 2015)
The third edition of The Parathyroids, led by a new stellar editorial team, has been thoroughly updated to reflect the considerable advances in just about every aspect of PTH biology over the past decade. It continues to be the authoritative reference that spans the basic science of parathyroid hormone treatment to major clinical disorders in a superb, single compendium. This translational resource is invaluable to graduate students, fellows, researchers, and research clinicians in the fields of endocrinology, bone biology, osteology, and rheumatology.